Control of Spatial Deposition of Electrospun Fiber Using Electric Field Manipulation. Issue 1 (March 2014) - Nurfaizey, Abdul Hamid; Stanger, Jonathan; Tucker, Nick; Buunk, Neil; Wood, Alan R.; Staiger, Mark P.
A significant challenge in the synthesis of uniform membranes via electrospinning is achieving a spatially uniform deposition of electrospun fibers. The problem is more pronounced in the case of a multi-spinneret system due to self repulsion between the jets. In this study, electric field manipulation ( via auxiliary electrodes) is explored as a potential technique for controlling the spatial deposition area of electrospun fiber. It was observed experimentally that the location and size of the deposition area can be moved linearly in response to the applied voltages at the auxiliary electrodes. Finite element analysis (FEA) was used to simulate the electric field strength and distribution at a given applied voltage and its effect on the flight path of electrospun fiber. Comparisons between experiments and simulations were made in evaluating the accuracy of simulations. The adaptation of this technique in production would provide a method of controlled deposition for producing uniform electrospun fiber membranes.